Methamphetamine - Shukla, Rashi K.
"Methamphetamine: A Love Story presents an insider's view into the lived experience of immersion in the world of methamphetamine. In-depth interviews were conducted with 33 adults formerly immersed in using, dealing, and manufacturing. Detailed accounts bring insight into the intoxicating aspects of the lifestyle including sex, money, power, and the ability to create methamphetamine. Social networks and environment play an important role in shaping and influencing drug-related decisions. The transformation of the lifestyle from one that is intoxicating to one that becomes risky and ultimately dark explains the unsustainability and the challenges exiting the life"--Provided by publisher.
Introduction to darkness -- Pathways to methamphetamine -- Loving meth -- Dealing meth -- Manufacturing meth -- An intoxicating life -- A risky life -- A dark life -- Life after meth -- The journey ends -- Appendix: methamphetamine laboratory signs.
Keywords: Methamphetamine abuse; Drug traffic